2022
DOI: 10.3390/jcm11216304
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics in PI-RADS 3 Multiparametric MRI for Prostate Cancer Identification: Literature Models Re-Implementation and Proposal of a Clinical–Radiological Model

Abstract: PI-RADS 3 prostate lesions clinical management is still debated, with high variability among different centers. Identifying clinically significant tumors among PI-RADS 3 is crucial. Radiomics applied to multiparametric MR (mpMR) seems promising. Nevertheless, reproducibility assessment by external validation is required. We retrospectively included all patients with at least one PI-RADS 3 lesion (PI-RADS v2.1) detected on a 3T prostate MRI scan at our Institution (June 2016–March 2021). An MRI-targeted biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We found that only three patients in the Prostaflog ® group showed a significant reduction in total PSA value while having positive mpMRI findings (6%), compared with nine in the Serenoa Repens group (19.5%) (p < 0.001), thereby showing that the risk of lowering PSA caused by prostate cancer by means of a hormonal pathway is very low. After the introduction of mpMRI, the number of unnecessary prostate biopsies has decreased and the role of PSA as diagnostic marker of prostate cancer has been reduced [2,3,31]. However, the use of mpMRI is not yet widespread in all countries, and we therefore still need tools that enable us to differentiate if an elevated PSA is due to prostate cancer or inflammation [32].…”
Section: Discussionmentioning
confidence: 99%
“…We found that only three patients in the Prostaflog ® group showed a significant reduction in total PSA value while having positive mpMRI findings (6%), compared with nine in the Serenoa Repens group (19.5%) (p < 0.001), thereby showing that the risk of lowering PSA caused by prostate cancer by means of a hormonal pathway is very low. After the introduction of mpMRI, the number of unnecessary prostate biopsies has decreased and the role of PSA as diagnostic marker of prostate cancer has been reduced [2,3,31]. However, the use of mpMRI is not yet widespread in all countries, and we therefore still need tools that enable us to differentiate if an elevated PSA is due to prostate cancer or inflammation [32].…”
Section: Discussionmentioning
confidence: 99%
“…We found that only 3 patients in the Prostaflog ® group showed a significant reduction of total PSA value while having positive findings at mpMRI (6%) compared with 9 in the Serenoa Repens group (19.5%) (p<0.001), thereby showing that the risk of lowering PSA caused by prostate cancer by means of a hormonal pathway, is very low. After the introduction of mpMRI the number of unnecessary prostate biopsies have decreased and the role of PSA as diagnostic marker of prostate cancer is reduced [2,3,20]. However, the use of mpMRI is not yet widespread in all countries and we therefore still need tools that enable us to differentiate if an elevated PSA is due to prostate cancer or inflammation [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we explored the putative role of mpMRI radiomics in downgrading non-csPC PI-RADS 4/5 lesions. Many authors have focused on mpMRI radiomics to upgrade PI-RADS 3 lesions [26][27][28]. Nevertheless, to the best of our knowledge, only two studies have tried to apply MRI texture feature analysis to distinguish csPC in lesions scored as PI-RADS 4 and 5.…”
Section: Discussionmentioning
confidence: 99%